Association between dietary vitamin B2 intake and constipation: a nationwide cross-sectional study - Ma, Chuanyu; Ma, Ning; Lu, Hongyang; Huang, Tianye; Zhang, Jingtao; Luo, Minglei; Zhang, Kening (Frontiers in Medicine, 2025)
BackgroundA multitude of studies has suggested a possible link between the intake of dietary micronutrients and the incidence of constipation. Nevertheless, there exists a significant gap in research that specifically addresses the relationship between vitamin B2 and constipation. The present investigation seeks to explore the possible correlation between dietary intake of vitamin B2 and chronic constipation in adult participants surveyed in the National Health and Nutrition Examination Survey (NHANES).MethodsThis research leveraged data from the NHANES conducted between 2005 and 2010. Dietary intake information was obtained from participants through 24 h dietary recall interviews. Various statistical approaches, including weighted logistic regression, interaction tests, subgroup analyses, and restricted cubic spline, were utilized to examine the relationship between dietary vitamin B2 consumption and the occurrence of constipation.ResultsA comprehensive multiple logistic regression analysis that accounted for various confounding factors indicated that individuals with the highest quartile of vitamin B2 intake exhibited a significantly reduced risk of experiencing constipation (OR = 0.63; 95% CI, 0.47–0.84) in comparison to those situated in the lowest quartile. Furthermore, a continuous assessment of vitamin B2 intake demonstrated an inverse relationship with constipation (OR = 0.89, 95% CI, 0.81–0.98). The implementation of restricted cubic splines suggested a linear association between vitamin B2 consumption and constipation (P-non-linear = 0.7297, P-overall = 0.0224). Notably, subgroup analyses uncovered a significant interaction effect between vitamin B2 intake and alcohol consumption regarding constipation (Pfor interaction = 0.012).ConclusionThis investigation highlights an inverse relationship between the dietary intake of vitamin B2 and constipation within the adult population of the United States.